UPAYA MENINGKATKAN HASIL BELAJAR IPS MELALUI PEMBELAJARAN KOOPERATIF MODEL PERMAINAN SUSUN KATA PADA SISWA KELAS IV B MI AL MA'ARIF 02 SINGOSARI MALANG - Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
This study aims to describe the teacher's efforts in improving social studies learning outcomes through cooperative learning with word stacking game models in class IV B MI Al Maarif 02 Singosari. This type of research is classroom action research. The results showed that the increase in social studies learning outcomes with the implementation of cooperative learning strategies with the word stacking game model could be proven by the results of the percentage of observations on the implementation of learning by teachers from cycle I to cycle II which increased by 7.30%, from 83.80% to 91.10% with the success criteria are